Weed Control Programs for Xtend Soybeans in No-Tillage - D. E. Peterson; C. Thompson; C. L. Minihan (Kansas Agricultural Experiment Station Research Reports, 2017)
The development of glyphosate-resistant weeds has greatly complicated weed control in soybeans. Roundup Ready 2 Xtend (dicamba tolerant) soybeans provide growers an alternative herbicide option for preplant and postemergence weed control in no-tillage soybeans. Preplant programs that included dicamba provided excellent control of giant ragweed. All sequential programs provided excellent control of the weeds present in the experiment.
Keywords: Roundup Ready 2 Xtend soybeans; henbit; giant ragweed; Palmer amaranth; large crabgrass